2021
DOI: 10.1002/acr.24531
|View full text |Cite
|
Sign up to set email alerts
|

Association of Medication Access Difficulty and COVID‐19–Related Distress With Disease Flares in Rheumatology Patients During the COVID‐19 Pandemic

Abstract: Objective. Due to concerns of infection and medication disruptions during the COVID-19 pandemic, rheumatology patients at the pandemic epicenter were at risk of distress and poor health outcomes. We sought to investigate medication disruptions and COVID-19-related distress in the Bronx, New York shortly after the peak of the pandemic and determine whether factors related to the pandemic were associated with flares, disease activity, and overall health.Methods. In the month following the epidemic peak, we surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 12 publications
3
36
1
Order By: Relevance
“…Furthermore, associated repeated lockdown measures are also likely to decrease healthcare access and availability with a decrease in the number of people attending A&E services, 4 and reports of difficulties accessing medication. 8 Our findings are consistent with current evidence from a smaller sub-set of the studies examined here suggesting that females are more likely to experience disruption to planned surgery, medical procedures, or other medical appointments during lockdown. 12 Furthermore, our results show that older adults were more likely to report healthcare disruption as compared to their younger counterparts, especially disruptions to medical appointments and planned procedures or surgeries.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, associated repeated lockdown measures are also likely to decrease healthcare access and availability with a decrease in the number of people attending A&E services, 4 and reports of difficulties accessing medication. 8 Our findings are consistent with current evidence from a smaller sub-set of the studies examined here suggesting that females are more likely to experience disruption to planned surgery, medical procedures, or other medical appointments during lockdown. 12 Furthermore, our results show that older adults were more likely to report healthcare disruption as compared to their younger counterparts, especially disruptions to medical appointments and planned procedures or surgeries.…”
Section: Discussionsupporting
confidence: 89%
“…Disruption to pharmacological treatments has also been reported with delays in accessing medication. 7,8 However, a comprehensive assessment of inequalities in healthcare disruption in the community is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are not fully in line with a EULAR-initiated survey among healthcare professionals that reported a negative impact of the pandemic on T2T strategies due to perceived postponement of treatment decisions and less likelihood to initiate a bDMARD or targeted synthetic DMARD [ 1 ]. However, important factors identified in this and other surveys include diagnostic delay and a shortage of DMARDs, including hydroxychloroquine or tocilizumab [ 1 , 15 ], both of which were less relevant in our study, where the majority of patients had established disease (10 years disease duration) and a shortage of medicines has not played any major role during the pandemic in Denmark. In the current study, the T2T strategy was mainly evaluated as the proportion of patients in remission.…”
Section: Discussionmentioning
confidence: 71%
“…The importance of this cannot be overemphasized and is illustrated in a survey of pediatric rheumatologists from the Paediatric Rheumatology European Society, indicating that a third of patients experienced a flare or exacerbation of their illness because of delays to appointments during the pandemic (43). Similarly, a study of adult and pediatric patients from a single center in New York City early in the pandemic found that 40% of patients reported experiencing a flare in the prior month and that patients reported experiencing anxiety when coming in for routine or urgent visits regarding their rheumatic conditions (46). New guidance has been provided to improve telemedicine assessments, including standardizing the musculoskeletal physical exam using the video version of pGALS, V-pGALS (47).…”
Section: Highmentioning
confidence: 99%
“…The task force also recognized the increased prevalence of anxiety and depression in patients with PRD as compared to the general population (53)(54)(55) and addressed concerns about additional emotional distress related to the COVID-19 pandemic (56). Additional evidence has accumulated indicating the adverse impact of the pandemic era on the mental health of children with PRD and particularly patients within Black and Latinx populations (46,(57)(58)(59). Rheumatology providers should be aware of the heightened emotional burden posed by the pandemic, including fears of becoming infected, having a family member infected, potential risks from medications, concerns about social isolation, and potential financial hardships.…”
Section: Highmentioning
confidence: 99%